Professional foster carer and committed parent: role conflict and role enrichment at the interface between work and family in long‐term foster care. Issue 1 (3rd January 2013) - Schofield, Gillian; Beek, Mary; Ward, Emma; Biggart, Laura
Abstract In the literature on work–family balance, role and boundary issues are commonly discussed in relation to parents who work outside of the home. Work and family are considered as two different spheres of activity, with different role identities and cultural meanings. For foster carers, however, in very significant ways, their family is their work and their work is their family – so roles are not so clearly separated and boundaries are not so clearly defined. This paper reviews theoretical approaches to the work–family interface and draws on qualitative data from 40 interviews with long‐term foster carers. It provides an analysis of their accounts of their roles as professional carers and/or committed parents to explore how they manage different and potentially contradictory role identities. The study found that foster carers primarily identified as carers or as parents, but that some foster carers could move flexibly between these roles while others could not. For foster carers who could be flexible, the two roles enriched each other rather than causing stress and role conflict. Implications for supporting professional foster carers who can also meet the parenting needs of long‐term foster children are discussed.